Three decades of Mediterranean mixed layer depth change: basin trends and regional contrasts - Babagolimatikolaei, Javad (Frontiers in Marine Science, 2025)
IntroductionThe mixed layer depth (MLD) regulates air–sea heat fluxes, nutrient entrainment, and ecosystem dynamics in the Mediterranean Sea, making its long-term evolution a sensitive indicator of climate-driven changes in ocean stratification and surface thermal conditions.MethodsUsing a high-resolution Mediterranean physical reanalysis and daily mixed-layer estimates (1990–2019), we quantify basin-wide changes in MLD, their seasonal and regional variability, and the physical drivers behind them.ResultsAcross the Mediterranean, MLD exhibits strong seasonal and interannual variability, but a persistent long-term shoaling of ≈0.5–0.6 m per decade is evident. This trend is most robust in spring and late autumn (notably April, November, and December) and is linked primarily to enhanced near-surface stratification driven by surface warming and subsurface salinification; surface Brunt–Väisälä frequency (N²) increased by ≈4.26 × 10⁻⁷ s⁻² per decade in the upper 0–50 m. Changes in wind stress are spatially heterogeneous and too weak to explain the basin-scale shoaling, although localized winter intensification (e.g., Gulf of Lion) produced episodic deepening and strong convection in the 1990s–2000s. Sub-basin contrasts are pronounced: the Levantine Basin shows consistent shoaling, the Southern Adriatic displays modest variability, and the Northwestern Mediterranean experienced transient deepening episodes linked to dense water formation.DiscussionContinued shoaling of the mixed layer has important implications for winter ventilation, nutrient supply to the euphotic zone, and the vulnerability of Mediterranean ecosystems to prolonged marine heatwaves.